(untitled) (Philological Studies, 2019)
In this work, the pattern of initiation in Macedonian and Bulgarian epic poems about Banovic Sekula was considered. It was done according to the customs that appear only in the eastern area of poems about this hero. The basic reason for Sekula’s inclusion into the pattern of initiation is his youth. Therefore, the differences in typological determination of Sekula as a young hero, in the eastern and western area of poems, are studied. The ritual base of the pattern of initiation is recognized, typical for the eastern cultural and historical areal – ʻsnihacestvo’ and ʻprvice’.